A prospective observational study comparing outcomes application of low-frequency pulse electrical combined with target-oriented rehabilitation therapy in postoperative nerve function rehabilitation of patients with distal humeral fracture and radial nerve injury - Shi, Shaoyan; Ou, Xuehai; Du, Xiaolong (Frontiers in Neurology, 2024)
Objective: To compare the effect of low-frequency pulse electrical stimulation combined with target-oriented rehabilitation therapy and single low-frequency pulse electrical stimulation therapy on postoperative neurological improvement in patients with radial nerve injury and humeral condylar fracture. Methods: A total of 88 patients with humeral condyle fracture and radial nerve injury admitted to our hospital were randomly divided into a combined group and a control group, with 44 patients in each group. The patients in the combined group received low-frequency pulse electrical stimulation combined with target-oriented rehabilitation therapy, while those in the control group received low-frequency pulse electrical stimulation therapy. Results: After treatment, the recovery rate in the combined group(77.27%) was higher than that in the control group (50.00%)(P<0.05). There was no significant difference in finger extensor and wrist extensor muscle strength before treatment between the two groups (P>0.05). After treatment, both groups showed improvement compared to before treatment (P<0.05), and the recovery in the combined group was better than that in the control group (P<0.05). There was no significant difference in MCV and amplitude before treatment between the two groups (P>0.05). After treatment, both groups showed improvement compared to before treatment (P<0.05), and the recovery in the combined group was better than that in the control group (P<0.05). The fracture healing time in the combined group was shorter than that in the control group (P<0.05). During the treatment period, there was 1 case of infection and 1 case of joint pain in the combined group, with a complication rate of 4.55%. In the control group, there was 1 case of infection and 2 cases of joint pain, with a complication rate of 6.82%. There was no significant difference in the complication rate between the two groups (P>0.05). The DHI score in the combined group was better than that in the control group (P<0.05). The ESCA score in the combined group was better than that in the control group (P<0.05). Conclusion: Low-frequency pulse electrical stimulation combined with target-oriented rehabilitation therapy can promote muscle strength and functional recovery after radial nerve injury, accelerate fracture healing time, and no additional risk of complications.